Low Acid Bio-Oil from Para Rubber Seeds Produced via Catalytic Pyrolysis with V-modified Silica Catalyst - Neumlang, Pawarisa; Khadthiphong, Anucha; Pimpakhun, Kaewkran; Kaewbuadee, Jenjira; Chaichana, Ekrachan (Food and Applied Bioscience Journal, 2018)
Bio-oil produced from pyrolysis of biomass is considered one of the most important renewable fuels due to wide availability, cheaper cost compared to fossil fuels, reduction of waste in landfills and carbon neutrality. In this study, bio-oil from Para rubber seeds (shell and flesh) was produced via a conventional pyrolysis with a 0.5 L batch reactor at various temperatures (400–600°C). It was found that the temperature affected the bio-oil yields of both shell and flesh pyrolysis but in different manners. For shell pyrolysis, the bio-oil yield increased with increasing temperature from 400 to 500°C and decreased when the temperature reached 600°C. For flesh pyrolysis, the bio-oil yield increased with increasing temperature until 600°C. However, the obtained bio-oil from those processes has low quality with high acidity (pH 2.6–5.0) which causes corrosion to an engine if used as fuel. In order to improve its quality, catalytic pyrolysis with rice-husk derived silica modified with vanadium (SiO2/V) was introduced. It was found that the catalytic pyrolysis produced the bio-oil with a lower acidity (pH 8). It was due to SiO2/V leading to the reactions which reduce acidic compounds occurring in the pyrolysis system, thus decreasing acidity in the bio-oil. The catalytic pyrolysis here also provides bio-oil yield slightly higher than those from the non-catalytic pyrolysis at the same temperature (44.1 and 43.6 wt%), but lower heating value (36.4 and 37.3 MJ/kg). With further modification, it is plausible that the obtained bio-oil from the catalytic pyrolysis in this study could be comparable to the commercial diesel fuel which pH is between 5.5 and 8.0, and heating value is roughly 45.5 MJ/kg. Thus, the bio-oil from pyrolysis of rubber seeds could be a potential candidate for renewable fuel.